2020
DOI: 10.1002/adma.201907208
|View full text |Cite
|
Sign up to set email alerts
|

An Unconventional Transient Phase with Cycloidal Order of Polarization in Energy‐Storage Antiferroelectric PbZrO3

Abstract: Antiferroelectric‐based dielectric capacitors are receiving tremendous attention for their outstanding energy‐storage performance and extraordinary flexibility in collecting pulsed powers. Nevertheless, the in situ atomic‐scale structural‐evolution pathway, inherently coupling to the energy storage process, has not been elucidated for the ultimate mechanistic understanding so far. Here, time‐ and atomic‐resolution structural phase evolution in antiferroelectric PbZrO3 during storage of energy from the electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 59 publications
(81 reference statements)
1
59
0
1
Order By: Relevance
“…Nonetheless, early work has demonstrated that the prototypical PbZrO 3 showed multiple soft-mode vibrations, which mainly involved trilinear coupling between vibrations of Pb cations and librations of oxygen octahedra 24 . Moreover, the very recent work on the electron-beam illumination induced phase transition in PbZrO 3 single crystals clearly showed the hierarchical evolution of oxygen octahedra 25 . Thus, as an important component in perovskite PbZrO 3 -based materials, the information of oxygen octahedra should be essentially taken into account for comprehending structure-property correlation and developing AFE/FiE theories.…”
mentioning
confidence: 93%
“…Nonetheless, early work has demonstrated that the prototypical PbZrO 3 showed multiple soft-mode vibrations, which mainly involved trilinear coupling between vibrations of Pb cations and librations of oxygen octahedra 24 . Moreover, the very recent work on the electron-beam illumination induced phase transition in PbZrO 3 single crystals clearly showed the hierarchical evolution of oxygen octahedra 25 . Thus, as an important component in perovskite PbZrO 3 -based materials, the information of oxygen octahedra should be essentially taken into account for comprehending structure-property correlation and developing AFE/FiE theories.…”
mentioning
confidence: 93%
“…Meanwhile, the defect core initiates an AFD‐to‐FD transition in a stripe region with width of ≈ b AF along x direction, which is characterized by y ‐direction transformation of oxygen shifts from (0 ↓ 0 ↑)/(0 ↑ 0 ↓) in the AFD state to (0 ↓ ↑ ↑)/(0 ↑ ↓ ↓) in the FD‐I state. [ 14 ] Herein, the zeros “0” marked by red solid line denote oxygen atoms locating at the centrosymmetric positions. This reveals that polar distortion occurs to the oxygen octahedral in the FD state, which generates a polarization with P S ≈ 3 µC cm −2 that essentially runs along [1¯00]normalO direction according to previous TEM measurement [ 14 ] (Figure S2b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] Herein, the zeros “0” marked by red solid line denote oxygen atoms locating at the centrosymmetric positions. This reveals that polar distortion occurs to the oxygen octahedral in the FD state, which generates a polarization with P S ≈ 3 µC cm −2 that essentially runs along [1¯00]normalO direction according to previous TEM measurement [ 14 ] (Figure S2b, Supporting Information). As the irradiation time increases to t = 20 s, the FD‐I state expands in unit‐cell wise along y direction, which is accompanied with dynamic size change of the defect core.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations